فهــم القــرآن الكريم بين مرتكزات العرف اللغوي وخصوصيات العرف القرآني - بوراس, نبيل (جامعة الوادي - University of Eloued, 2018)
تطرُق الدراسة قضية جوهرية ـ تتعلق بكتاب الله عز وجل ـ، متمثّلةً في الكشف عن المقاربة اللغوية بين خصوصية النص القرآني على مستوى الألفاظ والأساليب، وعلاقتها بمعهود الكلام العربي الأصيل، وأثر ذلك في الفهم الصحيح للقرآن الكريم، حيث تناول الباحث التعريف ببعض المصطلحات التي تتمحور حولها الدراسة ، وكذلك بسط القول بشأن ضوابط معرفة العرف القرآني، وخصائصه من ناحية الألفاظ وبعض الأساليب، مبرزا في ذلك كله علاقته الوطيدة بالعرف اللغوي. The study talks about a fundamental issue related to the Book of Allah Almighty, which is the disclosure of the linguistic convergence between the specificity of the Qur’anic text at the level of words and styles, and its relationship with the linguistic conventions of the Arab, and its effect on the correct understanding of the Holy Qur’an, where the researcher addressed the definition of some terms of the study, then Explaining the controls of knowing the Qur’anic habit, and its characteristics in terms of expressions and some styles, highlighting in all of this its close relationship with the linguistic habit.
مقال
Keywords: النص القرآني؛ العرف القرآني؛ العرف اللغوي؛ التفسير؛ الفهم; Quranic text; Quranic habit; Linguistic habit; Interpretation; Understanding